IL-17 polymorphisms and asthma risk: a meta-analysis of 11 single nucleotide polymorphisms. (26th November 2015) - Jin, Yan; Deng, Zaichun; Cao, Chao; Li, Longxiang
Abstract: Objective : There has been significant interest in the association between asthma and the polymorphisms of IL-17A and IL-17F for a period of time. This work aims to present a clearer relationship between asthma and the polymorphisms of IL-17A and IL-17F. Method : Searches were performed in Medline, EMBASE, and the Chinese National Knowledge Infrastructure (CNKI) databases. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the relationship between polymorphisms of IL-17A and IL-17F and asthma. Results : Nine studies comprising 3650 asthmatics and 3370 controls were included in this meta-analysis for all single nucleotide polymorphisms (SNPs) (2–6 per SNP). Our study examined the polymorphisms of IL-17F rs1889570 (C/T) (CC versus TT: OR = 0.55, 95%CI = 0.41–0.75; CT versus TT: OR = 0.54, 95%CI = 0.40–0.72; CC/CT versus TT: OR = 0.55, 95%CI = 0.42–0.72; CC versus CT/TT, OR = 1.83, 95%CI = 1.39–2.41), IL-17A rs4711998(A/G) (AA/AG versus GG: OR = 0.67, 95%CI = 0.46–0.98), and IL-17A rs3819024(A/G) (AA versus GG: OR = 1.77, 95%CI = 1.39–2.25) and found they were significantly related to the risk of asthma. Conclusion : Our systematic review showed that IL-17F rs1889570(C/T), IL-17A rs4711998(A/G) and IL-17A rs3819024(A/G) may be potential risk factors for asthma susceptibility.